Comparison between the Changes in the Plasma Fibrinogen and Plasminogen Levels Induced by a Moderate or High Initial Dose of Streptokinase - Amery, A; Donati, M. B; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1970)
Patients with thrombo-embolic diseases received a maintenance infusion of 0.1 × 106 u streptokinase (SK) h for at least 24 h; the infusion was started either with an initial dose of 0.25 × 106 u SK or an initial dose of 1.2 × 106 u SK.Before the infusion no significant differences were found betv/een the groups studied here in regard to the plasma fibrinogen and plasminogen levels.The fibrinogen and plasminogen levels were significantly more depressed immediately after the high initial dose than immediately after the moderate initial dose.However, 24 h later, as a maintenance dose of 0.1 × 108 u SK was given in both groups, the number of patients with a plasma plasminogen level below 5% was not significantly (P more than 0.1) different. The subsequent evolution of the plasminogen level in the patients treated for 72 h was independent of the initial dose used. After 24 h infusion, the fibrinogen level was already raised in the patients receiving a high initial dose, while it was further decreased in the patients with a moderate initial dose. The subsequent evolution of the fibrinogen level, followed in the patients treated for 72 h, showed that at 48 h the fibrinogen level was not significantly higher in the group receiving 1.2 × 108 u SK as initial dose than in the other group. At 72 h the fibrinogen level was nearly identical for both groups.